Behavioral plasticity mediates adaptation to changes in food provisioning following the COVID-19 lockdown in black-headed gulls (Larus ridibundus) - Xu, Hongying; Zhao, Xuebing; Jia, Ru; Chen, Lixia; Yang, Zeyu; Zhang, Guogang (Frontiers in Ecology and Evolution, 2022)
The 2020 COVID-19 lockdown provides an opportunity to assess how the anthropause affected the behavior of birds. Black-headed gulls (Larus ridibundus) wintering at Dianchi Lake (Yunnan Province, southwestern China) prefer to forage on easily accessible human-provided food at various sites along the lake. Following the closure of the lake because of the pandemic, synthetic food was provided at a single location. We expected that the home range size and distribution of gulls would change in response to these changes in food provisioning. A total of 91 gulls were tagged with satellite transmitters in November 2018 and March 2019, and their movements were tracked during the winter months. We analyzed their home range size and spatial distribution in four periods, SCP2019, SOP2019, SCP2020, and SOP2020 (Scenic Opening/Closing Period in 2019/2020), and the difference between SOP2019 and SCP2019 was used as the control group. The eutrophication level in the wintering periods “Nov. 2018–Apr. 2019” and “Oct. 2019–Apr. 2020” was determined using the Normalized Difference Vegetation Index (NDVI), and the coverage ratio of algal blooms and NDVI were used as indicators of the amount of naturally available food. The home range sizes of gulls were reduced in SCP2020 compared with SOP2019, SCP2019, and SOP2020. The gulls were most abundant in the 600–900 m buffer zone and least abundant in the 0–300 m buffer zone in SCP2019; they were most abundant in the 0–300 m buffer zone and least abundant in the 900–2000 m buffer zone in SCP2020. These patterns were consistent with variation in the NDVI and the coverage ratio of algal blooms among buffer zones. Changes in wintering behaviors in SCP2020 relative to other periods suggested that gulls modified their behavior following anthropause-related changes in the distribution and provisioning of food. Our findings provide insights into the role of behavioral plasticity in mediating adaptation to changes in human activities in birds.